Hydration, thermoregulation, and performance effects of two sport drinks during soccer training sessions - Siegler, J. C.; Mermier, C. M.; Amorim, F. T.; Lovell, R. J.; McNaughton, L. R.; Robergs, R. A. (The Journal of Strength and Conditioning Research, 2008)
In the present study, we aimed to compare the thermoregulatory response and soccer-specific training performance aspects of two commercially available sport drinks, both of similar carbohydrate concentration, but one containing 5.2% glycerol. Ten players participated in two similar outdoor training sessions and were randomly assigned to each of two drinks: a carbohydrate (C) beverage or a carbohydrate-glycerol (CG) beverage. Players consumed 500 mL of C or CG 30 minutes pre-exercise and at half-time. Pre- and postexercise body mass, core temperature (CT), and heart rate (HR) were recorded, and urine and blood samples were taken. No difference was observed between days for wet bulb globe temperature (session 1: 17.0 +/- 1.1[degrees]C, session 2: 16.9 +/- 1.1[degrees]C; P = 0.944). The degree of dehydration (% [DELTA] BM) was greater after the C trial (P = 0.041). Similarly, percent change in plasma volume was greater in the C trial (P = 0.049). No overall main affect was observed between CT and mean exercise HRs during either training session (CT: P = 0.350; mean HR: P = 0.256), and there was no difference observed between groups in time to failure during the session-ending fatigue test (P = 0.547). Ingestion of a CG beverage provided players with better hydration than C alone. However, if training sessions are short (<75 minute), with adequate time for recovery, both drinks are sufficient for maintaining performance intensities during soccer-specific training.